Improving Student Understanding Through the Development of Teaching Curriculum Textbooks for Madrasah Ibtidaiyah Teacher Education Learning Curriculum - Nuzulia, Nuril (Madrosatuna: Journal of Islamic Elementary School, 2023)
Development of Learning Curriculum Textbooks to Increase Madrasah Ibtidaiyah Teacher Education Students' Understanding of Learning Curriculum subjects at UIN Maulana Malik Ibrahim Malang is one of the means to help students understand and improve pedagogical abilities. The need to provide interesting and creative learning media in a lesson that aims to increase students' understanding and grades is one of the reasons behind this development research. This research and development method uses research and development (R&D) research. The procedure for developing this research uses a model, namely the Borg and Gall model. This research was conducted at the Madrasah Ibtidaiyah Teacher Education Study Program. Data collection techniques in this study were tests and observations. The data obtained were analyzed quantitatively and qualitatively. The development results were a book, "Introduction to the Learning Curriculum," for Madrasah Ibtidaiyah Teacher Education students. (1) the results of this research and development meet the valid criteria with the acquisition of validity, material experts obtain 90%, and design experts obtain 88% (2) trial results to assess the attractiveness of the book "Introduction to Learning Curriculum" developed for students in the Teacher Education Study Program Madrasah Ibtidaiyah by 90%. (3) student learning outcomes increased, as seen from the pre-test results of 71.90 and the post-test score of 87.10; it can be said that the book "Introduction to Learning Curriculum" is appropriate for students.